2014
DOI: 10.1039/c4cp01107d
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurements of the total rate constant of the reaction NCN + H and implications for the product branching ratio and the enthalpy of formation of NCN

Abstract: The overall rate constant of the reaction (2), NCN + H, which plays a key role in prompt-NO formation in flames, has been directly measured at temperatures 962 K < T < 2425 K behind shock waves. NCN radicals and H atoms were generated by the thermal decomposition of NCN3 and C2H5I, respectively. NCN concentration-time profiles were measured by sensitive narrow-line-width laser absorption at a wavelength of λ = 329.1302 nm. The obtained rate constants are best represented by the combination of two Arrhenius exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 45 publications
6
49
0
Order By: Relevance
“…It has therefore been synthesized directly in high purity in the gas phase, according to BrCN(g) + NaN 3 (s) -NCN 3 (g) + NaBr(s), using a method described in detail in ref. 22. After an 8 h reaction time the remaining BrCN impurities were usually o3% according to FTIR analysis.…”
Section: Ncn Precursormentioning
confidence: 99%
“…It has therefore been synthesized directly in high purity in the gas phase, according to BrCN(g) + NaN 3 (s) -NCN 3 (g) + NaBr(s), using a method described in detail in ref. 22. After an 8 h reaction time the remaining BrCN impurities were usually o3% according to FTIR analysis.…”
Section: Ncn Precursormentioning
confidence: 99%
“…In combustion chemistry, the kinetics of the cyanonitrene radical, NCN, has recently attracted attention [4][5][6][7][8][9][10][11] because NCN is considered an important intermediate in the formation of so-called prompt NO in hydrocarbon flames under fuel-rich conditions [12][13][14][15][16][17][18][19][20]. Cyanonitrene is a linear diradical with a 3 − g electronic ground state [21,22] and was shown to be formed under combustion conditions in the spin-allowed reaction CH(…”
Section: Introductionmentioning
confidence: 99%
“…These studies include the reactions NCN + NO, NO 2 [4], NCN + NCN, O, and M [5] as well as NCN + H [6] and NCN + H 2 [7]. The only other direct study reported in [14].…”
Section: Introductionmentioning
confidence: 93%
“…In contrast to φ, the rate constant k 7 for the assumed reformation of NCN has been found to be nearly temperature independent. It is therefore unfeasible that NCN is formed through the simple reverse of reaction (6), which should be temperature dependent as well. Hence, it can be speculated that NCN reformation takes actually place through a reaction sequence according to 3 NCNOO → 1 NCNOO → 3 NCN + O 2 involving an intersystem crossing (ISC) process.…”
mentioning
confidence: 99%
See 1 more Smart Citation